Bankruptcy oh bankruptcy: the Malaysians’ scenario / Anita Abu Hassan, Abdul Majeed Ahmad and Mohd Syazrul Hafizi Husin - Abu Hassan, Anita; Ahmad, Abdul Majeed; Husin, Mohd Syazrul Hafizi (Universiti Teknologi MARA, Kedah, 2022)
Bankruptcy. A dreaded term for everyone, especially those in the financial world. Bankruptcy is a word that is used to indicate the financial status of an individual and is a legal recognition given to someone who fails to pay their debts on time. In Malaysia, bankruptcy affairs are handled solely by the Malaysian Department of Insolvency (MDI). The individual's ability to enter into any contract will be revoked once he or she is declared bankrupt. As a result, a bankrupt would be unable to get employment, open a bank account, or even sign any document for oneself amongst others. They are also forbidden from leaving the country. It is the harshest penalty indeed for a person who does not follow through on a repayment commitment. However, there is slight leniency for the affected person. The bankrupt may engage in certain activities that are typically banned on them with the approval of the Director-General of MDI. For the legislative framework on bankruptcy, the first bankruptcy law was enacted in 1967 and further revised in 1988. The act was renamed the Insolvency Act 1967 in October 2017, with changes in several essential features. Changes to the law are made in accordance with the changes in the banking system, products or services offered by the financial institutions, and the lifestyle of the Malaysian. This paper attempts to discuss the scenario of Malaysians’ bankruptcy cases based on data obtained from 2016 to 2021. The number of bankruptcy cases by cause is illustrated below.